Building integrated connections for children, their families and communities edited by Karl Brettig, Margaret Sims. - Brettig, Karl.; Sims, Margaret (Newcastle : Cambridge Scholars, 2011)
Research and practice shows that many vulnerable children and families face more than one challenge and require more than one intervention. However our service system has evolved historically to deal with one thing at a time or to provide services from multiple sources.
Includes bibliographical references and index.
Keywords: Social work administration -- Congresses; Family social work -- Congresses; Dysfunctional families -- Services for -- Congresses; Abused children